2006
DOI: 10.1086/508980
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional Compressible Hydrodynamic Simulations of Vortices in Disks

Abstract: We carry out three-dimensional, high-resolution (up to 1024 2 ; 256) hydrodynamic simulations of the evolution of vortices in vertically unstratified Keplerian disks using the shearing sheet approximation. The transient amplification of incompressible, linear amplitude leading waves (which has been proposed as a possible route to nonlinear hydrodynamic turbulence in disks) is used as one test of our algorithms; our methods accurately capture the predicted amplification, converge at second order, and are free f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 28 publications
6
97
0
Order By: Relevance
“…Rayleigh's criterion for centrifugal stability applies only to fluids with constant density and therefore is not relevant to PPDs where the density falls off approximately like a Gaussian away from the midplane. One stability study of PPDs [4] argues that the stability of a PPD is governed by Rayleigh's centrifugal criterion, and another initial-value study of PPDs [5] with a very high spatial resolution did not show our new instability. However, both studies initialized the flow with constant density even though they both used an ideal gas equation of state.…”
Section: Why This Instability Was Not Discovered Previouslymentioning
confidence: 84%
“…Rayleigh's criterion for centrifugal stability applies only to fluids with constant density and therefore is not relevant to PPDs where the density falls off approximately like a Gaussian away from the midplane. One stability study of PPDs [4] argues that the stability of a PPD is governed by Rayleigh's centrifugal criterion, and another initial-value study of PPDs [5] with a very high spatial resolution did not show our new instability. However, both studies initialized the flow with constant density even though they both used an ideal gas equation of state.…”
Section: Why This Instability Was Not Discovered Previouslymentioning
confidence: 84%
“…Lower order codes can be diffusive enough that the energy introduced by aliasing may be immediately dissipated. Indeed, Shen et al (2006) highlight that they do not see any aliasing happening, and suggest that this is due to the high degree of numerical diffusivity in their code. This is of course a case of two negative features canceling each other.…”
Section: Appendix B: Testing For Aliasingmentioning
confidence: 94%
“…The solenoidality of the wave is guaranteed by initializing the velocity field through a streamfunction u = ∇×(ψẑ), with ψ = Ak −1 y sin k x x + k y y . We use the setup of Shen et al (2006), k x,0 = −16π/L x , k y = 4π/L y , with L x = L y = 0.5, A = 10 −4 , c s = Ω = ρ 0 = 1, γ = 7/5, and q = 3/2.…”
Section: Appendix B: Testing For Aliasingmentioning
confidence: 99%
“…Once excited, anticyclonic vortices are easily maintained in 2D simulations where, unless viscosity is present, they cannot decay and will instead merge, growing in size in a cascade of energy towards the largest scale of box (e.g., Johnson & Gammie 2005). However, three-dimensional studies in the context of protoplanetary disks found that tall vortex columns are destroyed, both in non-stratified (Shen et al 2006) and in stratified (Barranco & Marcus 2005) local boxes. This phenomenon is understood as a result of the elliptic instability (Crow 1970;Gledzel et al 1975;Kerswell 2002), by which the stretching term (ω · ∇)u, absent in 2D, breaks down elliptical streamlines such as vortical flow.…”
Section: Vortex Formation and Survivalmentioning
confidence: 99%